Galectin‐10, the protein that forms Charcot‐Leyden crystals, is not stored in granules but resides in the peripheral cytoplasm of human eosinophils. Issue 1 (28th February 2020) - Melo, Rossana C. N.; Wang, Haibin; Silva, Thiago P.; Imoto, Yoshimasa; Fujieda, Shigeharu; Fukuchi, Mineyo; Miyabe, Yui; Hirokawa, Makoto; Ueki, Shigeharu; Weller, Peter F.
Abstract: A predominant protein of human eosinophils is galectin‐10 (Gal‐10), also known as Charcot‐Leyden crystal protein (CLC‐P) because of its remarkable ability to form Charcot‐Leyden crystals (CLCs), which are frequently found in tissues from patients with eosinophilic disorders. CLC‐P/Gal‐10 is highly expressed in human eosinophils and considered a biomarker of eosinophil involvement in inflammation. However, the intracellular sites where large pools of CLC‐P/Gal‐10 constitutively reside are still unclear, and whether this protein is derived or not from eosinophil granules remains to be established. Here, we applied pre‐embedding immunonanogold transmission electron microscopy combined with strategies for optimal antigen and cell preservation and quantitative imaging analysis to investigate, for the first time, the intracellular localization of CLC‐P/Gal‐10 at high resolution in resting and activated human eosinophils. We demonstrated that CLC‐P/Gal‐10 is mostly stored in the peripheral cytoplasm of human eosinophils, being accumulated within an area of ∼250 nm wide underneath the plasma membrane and not within specific (secretory) granules, a pattern also observed by immunofluorescence. High‐resolution analysis of single cells revealed that CLC‐P/Gal‐10 interacts with the plasma membrane with immunoreactive microdomains of high CLC‐P/Gal‐10 density being found in ∼60% of the membrane area. Eosinophil stimulation with CCL11 or TNF‐α, which are known inducers of eosinophil secretion, did not change the peripheral localization of CLC‐P/Gal‐10 as observed by both immunofluorescence and immuno‐EM (electron microscopy). Thus, in contrast to other preformed eosinophil proteins, CLC‐P/Gal‐10 neither is stored within secretory granules nor exported through classical degranulation mechanisms (piecemeal degranulation and compound exocytosis). Abstract : Ascertains the intracellular sites of CLC‐P/Gal‐10 within resting and activated human eosinophils, revealing preformed stores associated with the peripheral cytosol and plasma membrane and not with granules. .